A FeCoNiCuVZrAl target material and preparation method thereof

Through steps such as aerosolization preparation and plasma sintering, the problem of matrix cracking caused by prone to agglomeration of high entropy alloys was solved, and a FeCoNiCuVZrAl alloy target material with high purity, high density and uniform structure was prepared.

CN119753595APending Publication Date: 2025-04-04TARFILM HI-TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411954538.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing high-entropy alloy preparation methods are difficult to achieve uniform distribution of alloys, which easily lead to agglomeration and matrix cracking.

Method used

The alloy powder is prepared by aerosolization, and the FeCoNiCuVZrAl alloy target is prepared through sieve mixing, presintering and plasma sintering.

Benefits of technology

The alloy is highly purified, dense, precise component control and uniform and unsegregated tissue, solving the matrix cracking problem caused by the prone to agglomeration of high-entropy alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753595A_ABST
    Figure CN119753595A_ABST
Patent Text Reader

Abstract

The present invention provides a FeCoNiCuVZrAl alloy target and a preparation method thereof, which relates to the field of metallurgical technology, and comprises the following steps: S1, preparation of alloy powder: preparing alloy powder by gas atomization of alloy liquid; S2, powder post-treatment: sieving and mixing the alloy powder obtained by gas atomization to obtain mixed powder; S3, plasma sintering: pre-sintering the mixed powder obtained by S2, and then plasma sintering; S4, machining: machining the blank after the processing in step S3, and cleaning to obtain the FeCoNiCuVZrAl target. The FeCoNiCuVZrAl alloy target prepared by the present invention has high purity, high density, precise composition control, and uniform organization without segregation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgy, and in particular to a FeCoNiCuVZrAl alloy target material and a preparation method thereof. Background Art

[0002] With the progress of society and the development of science and technology, higher and higher requirements are placed on the surface properties of materials. Not only are they required to have high hardness, wear resistance, and corrosion resistance, but they are also required to have high high temperature resistance to meet increasingly high engineering needs.

[0003] Applying a hard coating on the surface of a material is an economical and effective way to improve the surface performance of the material. At present, the research on high entropy alloys is increasing, and high entropy alloys require each component to be close to the equimolar ratio. The research on high entropy alloy films has gradually become a hot topic with the birth of high entropy alloys. At present, high entropy alloy films have outstanding mechanical properties and strong corrosion resistance. The preparation on the surface of tools and molds can not only extend the service life of the tools and molds, but also improve production efficiency.

[0004] High entropy alloy is a multi-principal-component, high-mixed-entropy alloy made of five or more metal and non-metal elements in equimolar or nearly equimolar ratios. It has excellent mechanical, chemical, electromagnetic and high-temperature oxidation resistance advantages, and is increasingly showing its superiority, especially in the field of magnetic recording media.

[0005] Currently, most methods for preparing high entropy alloys are based on melting and casting. This method makes it difficult to disperse the high entropy alloy in the matrix, easily causes the high entropy alloy to agglomerate, and the matrix is ​​prone to cracking.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The object of the present invention is to provide a FeCoNiCuVZrAl alloy target material and a preparation method thereof. The FeCoNiCuVZrAl alloy target material prepared by the present invention has high purity, high density, precise component control, uniform structure without segregation, and solves the problem of matrix cracking caused by easy agglomeration of high entropy alloys.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] The present invention provides a method for preparing a FeCoNiCuVZrAl target material, comprising the following steps:

[0010] S1. Preparation of alloy powder: preparing alloy powder by gas atomization of alloy liquid;

[0011] S2, powder post-processing: the alloy powder obtained by gas atomization is sieved and then mixed to obtain a mixed powder;

[0012] S3, plasma sintering: pre-sintering the mixed powder obtained in S2, and then plasma sintering to obtain a blank;

[0013] S4, machining: machining the blank processed in step S3, and obtaining a FeCoNiCuVZrAl target after cleaning.

[0014] Furthermore, on the basis of the above technical solution, the atomic percentages of Fe, Co, Ni, Cu, V, Zr and Al elements in the alloy liquid are all 5% to 35%.

[0015] Furthermore, based on the above technical solution, the atomic percentages of the elements in the alloy liquid are: Fe: 10-15%, Co: 10-15%, Ni: 10-15%, Cu: 12-18%, V: 10-15%, Zr: 20-25%, Al: 5-10%.

[0016] Further, based on the above technical solution, in step S1, the alloy liquid is obtained by smelting the alloy raw material;

[0017] Preferably, the alloy raw materials include Fe, Co, Ni, Cu, V, Zr and Al metal elements with a purity of 3N;

[0018] Preferably, the smelting includes: a temperature of 2100-2200° C., a holding time of 10-20 min, and a vacuum degree of (0.001-0.01) Pa.

[0019] Further, on the basis of the above technical solution, in step S2, aerosolization specifically includes the following steps:

[0020] In the vacuum atomization chamber, the inert gas breaks the alloy liquid into small droplets through the annular atomization nozzle, and the alloy powder is obtained after cooling;

[0021] And / or, in step S2, sieving refers to sieving through a 300-350 mesh sieve.

[0022] Further, on the basis of the above technical solution, the conditions for aerosolization include:

[0023] The inert gas is argon or helium, the gas pressure is 5-15MPa, and the vacuum degree is (0.001-0.01)Pa;

[0024] The particle size of the alloy powder obtained by gas atomization is 325-500 mesh.

[0025] Further, based on the above technical solution, step S3 specifically includes the following steps:

[0026] The mixed powder prepared by S2 is loaded into a mold, vacuumed, pre-sintered, and then heated for spark plasma sintering.

[0027] Further, on the basis of the above technical solution, the mold is a graphite mold; the vacuum degree is ≤5Pa;

[0028] And / or, the pre-sintering temperature is 400-450°C, the time is 10-15min, and the heating rate is 5-10°C / s;

[0029] And / or, the spark plasma sintering temperature is 850-1050° C., the pressure is 30-35 MPa, the heat preservation and pressure holding time is 15-25 min, the heating rate is 5-10° C. / s, the pulse current is 1500-2500 A, and the pulse duration is 5-20 ms.

[0030] Further, on the basis of the above technical solution, in step S4, the machining includes one or more of cutting, turning or grinding.

[0031] The present invention also provides a FeCoNiCuVZrAl target material prepared by the method for preparing the FeCoNiCuVZrAl target material as described above, wherein the relative density of the FeCoNiCuVZrAl target material is ≥99%.

[0032] The present invention provides a FeCoNiCuVZrAl target material and a preparation method thereof, and the beneficial effects are as follows:

[0033] The FeCoNiCuVZrAl alloy target obtained by the preparation method provided by the present invention has the advantages of high purity, high density, precise composition control, uniform organization and no segregation. In the technical scheme of the present invention, the alloy mixed powder is obtained by plasma sintering to quickly obtain a target with high purity, density and better microstructure, with low energy consumption, low cost and high yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 A process flow chart of a method for preparing a FeCoNiCuVZrAl target material provided by the present invention;

[0036] Figure 2 This is the microstructure diagram of the FeCoNiCuVZrAl target material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0038] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0039] According to a first aspect of the present invention, Figure 1 As shown, a method for preparing a FeCoNiCuVZrAl target material is provided, comprising the following steps:

[0040] S1. Preparation of alloy powder: preparing alloy powder by gas atomization of alloy liquid;

[0041] S2, powder post-processing: the alloy powder obtained by gas atomization is sieved and then mixed to obtain a mixed powder;

[0042] S3, plasma sintering: pre-sintering the mixed powder obtained in S2, and then plasma sintering to obtain a blank;

[0043] S4, machining: machining the blank processed in step S3, and obtaining a FeCoNiCuVZrAl target after cleaning.

[0044] As an optional embodiment of the present invention, the atomic percentages of Fe, Co, Ni, Cu, V, Zr and Al elements in the alloy liquid are all 5% to 35% (e.g., 10%, 15%, 20%, 25%, 30%, etc.).

[0045] Specifically, the present invention limits the atomic percentage of each element to 5% to 35% in order to ensure that the material has sufficient strength and hardness while maintaining good processing performance, and to meet the dual requirements of material performance and processability in practical applications. If it is higher than 35%, it may cause changes in the microstructure of the material, making the material more brittle and hard. Excessive element concentration will enhance the bonding force between grains, but it will also make the material more prone to fracture when subjected to external forces, thereby losing the ductility and plasticity required for processing. This brittle material will be difficult to achieve the desired processing effect in subsequent processing, such as forging, bending or cutting, and may even lead to processing failure.

[0046] As an optional embodiment of the present invention, the atomic percentage of each element in the alloy liquid is: Fe: 10-15% (for example, 11%, 12%, 13%, 14%, etc.), Co: 10-15% (for example, 11%, 12%, 13%, 14%, etc.), Ni: 10-15% (for example, 11%, 12%, 13%, 14%, etc.), Cu: 12-18% (for example, 13%, 14%, 15%, 16%, 17%, etc.), V: 10-15% (for example, 11%, 12%, 13%, 14%, etc.), Zr: 20-25% (for example, 21%, 22%, 23%, 24%, etc.), Al: 5-10% (for example, 6%, 7%, 8%, 9%, etc.).

[0047] Specifically, in the present invention, multiple elements are added to the alloy liquid in the form of single substances in order to more accurately control the composition ratio of the alloy and ensure that the chemical composition of the alloy meets the design requirements. The single elements can be more evenly distributed during the smelting process, which helps to improve the uniformity and performance of the alloy. In addition, during the smelting process, the single elements can be more conveniently melted and mixed with other elements, reducing the energy consumption and smelting time of the furnace, reducing the smelting cost, and simplifying the smelting process. If multiple elements are added to the alloy liquid in the form of alloys, since the element composition ratio of the alloy form has been fixed during the manufacturing process, it is difficult to fine-tune according to actual needs, which may cause the final alloy composition to deviate from the design requirements, and the multiple elements in the alloy form are difficult to be evenly distributed in the melt, which will affect the microstructure and macroscopic properties of the alloy, and the melting points of the multiple elements in the alloy form may be inconsistent. Higher temperatures or more complex processes are required during the smelting process to ensure that all elements are fully melted and evenly mixed. The smelting process is complex, the cost is high, and the production efficiency is low.

[0048] As an optional embodiment of the present invention, in step S1, the alloy liquid is obtained by smelting the alloy raw materials;

[0049] Preferably, the alloy raw materials include Fe, Co, Ni, Cu, V, Zr and Al metal elements with a purity of 3N;

[0050] Preferably, the smelting includes: a temperature of 2100-2200°C (such as 2120°C, 2150°C, 2170°C, etc.), a holding time of 10-20min (such as 12min, 14min, 16min, 18min, etc.), and a vacuum degree of (0.001-0.01)Pa (such as 0.002Pa, 0.004Pa, 0.006Pa, 0.008Pa, etc.).

[0051] As an optional embodiment of the present invention, in step S2, aerosolization specifically includes the following steps:

[0052] In the vacuum atomization chamber, the inert gas breaks the alloy liquid into small droplets through the annular atomization nozzle, and alloy powder is obtained after cooling.

[0053] As an optional embodiment of the present invention, the conditions for aerosolization include:

[0054] The inert gas is argon or helium, the gas pressure is 5-15MPa (such as 6MPa, 7MPa, 8MPa, 9MPa, 10MPa, 11MPa, 12MPa, 13MPa, 14MPa, etc.), and the vacuum degree is (0.001-0.01)Pa (such as 0.002Pa, 0.004Pa, 0.006Pa, 0.008Pa, etc.);

[0055] The particle size of the alloy powder obtained by gas atomization is 325-500 mesh.

[0056] Specifically, the present invention limits the gas pressure to 5-15 MPa in order to control the alloy powder particle size to 325-500 mesh. Alloy powder within this range helps to form finer grains during plasma sintering, thereby obtaining a better microstructure. If the pressure is too low, the powder particle size will be too coarse, and if the pressure is too high, the powder particle size will be too fine.

[0057] As an optional embodiment of the present invention, in step S2, sieving refers to sieving through a 300-350 mesh sieve.

[0058] As an optional implementation of the present invention, step S3 specifically includes the following steps:

[0059] The mixed powder prepared by S2 is loaded into a plasma sintering mold, evacuated, pre-sintered, and then heated for spark plasma sintering.

[0060] Specifically, the mixed powder prepared in step S2 has many types of elements, and the physical and chemical properties of the elements in the powder state may vary greatly. Therefore, the mixed powder needs to be pre-sintered. If the temperature is directly raised to 850-1050°C for spark plasma sintering, the following problems may occur:

[0061] (1) The powder particles are not fully combined, resulting in pores inside the sintered body;

[0062] (2) Due to differences in melting points, different elements may segregate at high temperatures, resulting in uneven composition within the sintered body;

[0063] (3) Powders that have not been pre-sintered may experience abnormal grain growth at high temperatures, resulting in an uneven microstructure of the sintered body;

[0064] (4) Thermal stress cracks: Due to the difference in thermal expansion coefficients, thermal stress may be generated during the sintering process, leading to the formation of cracks;

[0065] The emergence of the above problems will cause segregation of the material structure and reduce the density of the material.

[0066] As an optional embodiment of the present invention, the mold is a graphite mold; the vacuum degree is ≤5Pa (such as 1Pa, 2Pa, 3Pa, 4Pa, etc.);

[0067] And / or, the pre-sintering temperature is 400-450°C (such as 420°C, 440°C, 460°C, 480°C, etc.), the time is 10-15min (such as 11min, 12min, 13min, 14min, etc.), and the heating rate is 5-10°C / s (such as 6°C / s, 7°C / s, 8°C / s, 9°C / s, etc.);

[0068] Specifically, the present invention limits the pre-sintering temperature to 400-450°C, in order to achieve good densification, reasonable grain growth and controllable element diffusion within this temperature range, while avoiding the negative effects of excessively high temperatures; if the pre-sintering temperature is higher than 400-450°C, some grains will grow abnormally, and segregation may occur between a variety of different elements, which will not only reduce the uniformity of the material structure, but also reduce the density of the material. If the pre-sintering temperature is too high, it will also increase the internal thermal stress, thereby causing the risk of cracks or deformation; on the contrary, if the pre-sintering temperature is lower than 400-450°C, the atomic diffusion rate of a variety of elements will slow down, affecting the subsequent spark plasma sintering process, and ultimately affecting the density of the material.

[0069] And / or, the spark plasma sintering temperature is 850-1050°C (such as 870°C, 900°C, 910°C, 930°C, 950°C, 970°C, 990°C, 1000°C, 1010°C, 1030°C, etc.), the pressure is 30-35MPa (such as 31MPa, 32MPa, 33MPa, 34MPa, etc.), and the heat preservation and pressure holding time is 15-25min (such as 16min, 18min, 2 0min, 22min, 24min, etc.), the heating rate is 5-10℃ / s (such as 6℃ / s, 7℃ / s, 8℃ / s, 9℃ / s, etc.), the pulse current is 1500-2500A (such as 1700A, 1900A, 2100A, 2300A, etc.), and the pulse duration is 5-20ms (such as 7ms, 9ms, 10ms, 11ms, 13ms, 15ms, 17ms, 19ms, etc.).

[0070] Specifically, the present invention limits the heating rate of pre-sintering and spark plasma sintering to 5-10°C / s, which helps to keep the temperature gradient inside the material within a reasonable range, thereby reducing the generation and accumulation of thermal stress, avoiding material fracture, and also helps to control the growth rate of grains, thereby obtaining a uniform and fine grain structure. If the heating rate is too fast, that is, more than 10°C / s, internal stress will be rapidly generated inside the alloy material due to the excessive temperature gradient. These internal stresses may cause microcracks or fractures inside the material, especially in the process of increasing the material from room temperature to the sintering temperature, the accumulation of thermal stress may exceed the bearing capacity of the material, thereby seriously affecting the integrity and mechanical properties of the material. If the heating rate is too slow, that is, less than 5°C / s, although the generation of internal stress can be reduced, the sintering efficiency will be significantly reduced, and the slow heating will lead to a prolonged sintering process, increasing energy consumption and production costs, and the heating rate is too slow, which will also lead to insufficient diffusion of elements, thereby affecting the microstructure of the material.

[0071] Furthermore, the present invention limits the pressure of the spark plasma sintering process to 30-35MPa, which can effectively promote the growth and densification between powder particles. If the pressure is too high, it will accelerate the growth of grains, causing abnormal enlargement of grains, relatively reducing the grain boundary area, further reducing the barrier effect of grain boundaries on dislocations, causing the material structure to become uneven and segregated. If the pressure is too low, it will lead to problems such as insufficient densification of grains, slow sintering speed, weak grain bonding and microstructural defects.

[0072] Furthermore, the present invention limits the holding time to 15-25 minutes in order to ensure that the material can reach a suitable degree of densification during the sintering process, while avoiding abnormal grain growth, so as to obtain a sintered body with an ideal microstructure and performance. If the holding time is too short, the bonding between the powder particles may not be sufficient, resulting in a low density and high porosity of the sintered body. On the other hand, if the holding time is too long, it may cause excessive grain growth, weaken the bonding force between the grains, make the material structure uneven and segregate more, and reduce the density of the material.

[0073] Furthermore, the pulse current of the present invention is set to 1500-2500A in order to achieve uniform growth of grains and sufficient sintering of materials during the sintering process, thereby ensuring that the sintered body has high density and excellent performance. If the pulse current is too high, exceeding the range of 2500A, it may cause the grains to grow too fast, and the grain size and distribution become uneven, which will cause micro cracks and stress concentration inside the material, reducing the density of the material. On the contrary, if the pulse current is too low, below 1500A, it may lead to an insufficient sintering process and insufficient bonding between the powder particles, resulting in low density and high porosity of the sintered body, affecting the overall performance and stability of the material.

[0074] Furthermore, the present invention sets the pulse duration to 5-20ms, in order to ensure that the material can obtain appropriate heat input during the sintering process, promote the uniform growth of grains, and maintain the high density of the sintered body, thereby obtaining a sintered body with excellent performance. If the pulse duration is too long, exceeding 20ms, then the grains may grow abnormally during the sintering process, making the material structure uneven and segregated. On the other hand, if the pulse duration is too short, less than 5ms, it may not provide enough heat to promote the effective bonding between powder particles, resulting in too low density of the sintered body, affecting the density and mechanical properties of the material.

[0075] As an optional embodiment of the present invention, in step S4, the machining includes one or more of cutting, turning or grinding.

[0076] According to a second aspect of the present invention, there is provided a FeCoNiCuVZrAl target material prepared by the method for preparing the FeCoNiCuVZrAl target material as described above, wherein the relative density of the FeCoNiCuVZrAl target material is ≥99%.

[0077] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0078] Example 1

[0079] S1. Preparing FeCoNiCuVZrAl alloy powder: According to atomic percentage, 15% of Fe, 14% of Co, 10% of Ni, 17% of Cu, 12% of V, 25% of Zr and 7% of Al, all of which have a purity of 3N, are melted to obtain a molten alloy;

[0080] The melting temperature is 2100°C, the holding time is 15 min, and the vacuum degree is 0.01 Pa;

[0081] In the vacuum atomization chamber, argon gas breaks the alloy liquid into small droplets through the annular atomization nozzle, and alloy powder is obtained after cooling;

[0082] Among them, the gas pressure is 10MPa and the vacuum degree is 0.01Pa;

[0083] The particle size of the alloy powder obtained by gas atomization is in the range of 325-500 mesh.

[0084] S2. Powder post-treatment: the alloy powder obtained by gas atomization is sieved through -325 mesh, and the powder under the -325 mesh is mixed to obtain a mixed powder;

[0085] S3, plasma sintering: the mixed powder is loaded into a plasma sintering mold, evacuated to ≤5Pa, heated to 420°C at a rate of 5°C / s for pre-sintering for 12min, and then heated to 950°C at a rate of 5°C / s for spark plasma sintering, with a pressure of 35MPa, a heat and pressure holding time of 20min, a pulse current of 1700A, and a pulse duration of 15ms to obtain a blank;

[0086] S4, machining: machining the blank after the plasma sintering treatment in step 3, and obtaining the desired finished product after cleaning.

[0087] like Figure 2 As shown, the target material prepared in this embodiment has uniform structure and high density, and its relative density is 99.3%.

[0088] Embodiment 2:

[0089] S1. preparing FeCoNiCuVZrAl alloy powder: according to atomic percentage, 13% Fe, 15% Co, 15% Ni, 15% Cu, 14% V, 23% Zr and 5% Al blocks with purity of 3N are melted to obtain alloy liquid;

[0090] The melting temperature is 2200°C, the holding time is 10 min, and the vacuum degree is 0.01 Pa;

[0091] In the vacuum atomization chamber, helium gas breaks the alloy liquid into small droplets through the annular atomization nozzle, and alloy powder is obtained after cooling;

[0092] Among them, the gas pressure is 5MPa and the vacuum degree is 0.01Pa;

[0093] The particle size of the alloy powder obtained by gas atomization is in the range of 325-500 mesh.

[0094] S2. Powder post-treatment: the alloy powder obtained by gas atomization is sieved through -325 mesh, and the powder under the -325 mesh is mixed to obtain a mixed powder;

[0095] S3, plasma sintering: the mixed powder is loaded into a plasma sintering mold, evacuated to ≤5Pa, heated to 400°C at a rate of 6°C / s for pre-sintering for 15min, and then heated to 1000°C at a rate of 10°C / s for spark plasma sintering, with a pressure of 35MPa, a heat and pressure holding time of 25min, a pulse current of 1500A, and a pulse duration of 20ms to obtain a blank;

[0096] S4, machining: machining the blank after the plasma sintering treatment in step 3, and obtaining the desired finished product after cleaning.

[0097] The relative density of the target material prepared in this embodiment is 99.5%.

[0098] Embodiment 3:

[0099] S1. preparing FeCoNiCuVZrAl alloy powder: according to atomic percentage, 14% Fe, 13% Co, 15% Ni, 18% Cu, 10% V, 23% Zr and 7% Al blocks with a purity of 3N are melted to obtain alloy liquid;

[0100] The melting temperature is 2150℃, the holding time is 10min, and the vacuum degree is 0.01Pa;

[0101] In the vacuum atomization chamber, argon gas breaks the alloy liquid into small droplets through the annular atomization nozzle, and alloy powder is obtained after cooling;

[0102] Among them, the gas pressure is 15MPa and the vacuum degree is 0.01Pa;

[0103] The particle size of the alloy powder obtained by gas atomization is in the range of 325-500 mesh.

[0104] S2. Powder post-treatment: the alloy powder obtained by gas atomization is sieved through -325 mesh, and the powder under the -325 mesh is mixed to obtain a mixed powder;

[0105] S3, plasma sintering: the mixed powder is loaded into a plasma sintering mold, evacuated to ≤5Pa, heated to 450°C at a rate of 6°C / s for pre-sintering for 10min, and then heated to 950°C at a rate of 6°C / s for spark plasma sintering, with a pressure of 35MPa, a heat and pressure holding time of 15min, a pulse current of 2500A, and a pulse duration of 5ms to obtain a blank;

[0106] S4, machining: machining the blank after the plasma sintering treatment in step 3, and obtaining the desired finished product after cleaning.

[0107] The relative density of the target material prepared in this embodiment is 99.3%.

[0108] Comparative Example 1

[0109] (1) Preparation of alloy powder: According to atomic percentage, Fe15%, Co14%, Ni10%, Cu17%, V12%, Zr25% and Al7% with a purity of 3N and a particle size of -325 mesh were mixed by ball milling to obtain the required alloy powder.

[0110] (2) Plasma sintering: the mixed alloy powder is loaded into a plasma sintering mold, evacuated to ≤5 Pa, heated to 420 °C at a rate of 5 °C / s for pre-sintering for 12 min, and then heated to 950 °C at a rate of 6 °C / s for spark plasma sintering, with a pressure of 35 MPa, a holding time of 20 min, a pulse current of 1700 A, and a pulse duration of 15 ms to obtain a blank;

[0111] (3) Machining: Machining the blank obtained in step 2, and obtaining the desired finished product after cleaning.

[0112] The relative density of the target material prepared in this comparative example is 105%.

[0113] Compared with the technical solution for preparing the alloy target material in Example 1, the powders are directly mixed by the ball milling method, and the densities of various powders vary greatly, and segregation is likely to occur during the mixing process. The obtained alloy target material not only has segregation on the surface, but also has uneven internal structure distribution of the alloy and the presence of areas with higher density, so that the relative density of the obtained target material is greater than 100%.

[0114] Comparative Example 2:

[0115] The main difference between this comparative example and Example 1 is that the sintering method adopted in step S3 is hot isostatic pressing sintering, and the specific steps are:

[0116] S1. preparing FeCoNiCuVZrAl alloy powder: according to atomic percentage, 15% Fe, 14% Co, 10% Ni, 17% Cu, 12% V, 25% Zr and 7% Al blocks with a purity of 3N are melted to obtain alloy liquid;

[0117] The melting temperature is 2100°C, the holding time is 15 min, and the vacuum degree is 0.01 Pa;

[0118] In the vacuum atomization chamber, argon gas breaks the alloy liquid into small droplets through the annular atomization nozzle, and alloy powder is obtained after cooling;

[0119] Among them, the gas pressure is 10MPa and the vacuum degree is 0.01Pa;

[0120] The particle size of the alloy powder obtained by gas atomization is in the range of 325-500 mesh.

[0121] S2. Powder post-treatment: the alloy powder obtained by gas atomization is sieved through -325 mesh, and the powder under the -325 mesh is mixed to obtain a mixed powder;

[0122] S3, hot isostatic pressing: the mixed powder obtained in step S2 is placed in a bag for hot isostatic pressing at a temperature of 1000° C., a pressure of 130 MPa, and a heat preservation and pressing time of 5 h to obtain a blank;

[0123] S4, machining: machining the blank after the hot isostatic pressing treatment in step S3, and obtaining the desired finished product after cleaning.

[0124] The relative density of the target material prepared in this comparative example is 102%.

[0125] Compared with the technical solution for obtaining the alloy target material in Example 1, in Comparative Example 2, due to the excessive pressure requirement and long holding time during the hot isostatic pressing process, not only the preparation cost is high, but also under high pressure, the grains are abnormally enlarged, resulting in an uneven material structure and the presence of high-density areas inside, so that the relative density of the obtained target material is greater than 100%.

[0126] Comparative Example 3

[0127] The main difference between this comparative example and Example 1 is that in step S3, the mixed powder in step S2 is directly heated to 950° C. for spark plasma sintering without pre-sintering treatment, and the remaining operating steps and technical parameters are the same as those in Example 1.

[0128] The relative density of the target material prepared in this comparative example is 95%.

[0129] Compared with the embodiment, in this comparative example, since no pre-sintering treatment is performed in step S3, the elements are not sufficiently combined and segregation occurs, thereby reducing the density of the material, and ultimately causing the relative density of the prepared target material to be much lower than that of embodiment 1.

[0130] Comparative Example 4

[0131] The main difference between this comparative example and Example 1 is that in step S3, the heating rates of pre-sintering and spark plasma sintering are both 2°C / s, and the remaining operating steps and technical parameters are the same as those of Example 1.

[0132] The relative density of the target material prepared in this comparative example is 99%.

[0133] Compared with Example 1, the temperature rise rate of pre-sintering and spark plasma sintering in this comparative example is too low, resulting in insufficient diffusion of various elements in the material, affecting the microstructure of the material, thereby reducing the density of the material, and ultimately resulting in the relative density of the obtained target material being lower than that in Example 1.

[0134] Comparative Example 5

[0135] The main difference between this comparative example and Example 1 is that in step S3, the pressure of the spark plasma sintering process is 40 MPa, and the remaining operating steps and technical parameters are the same as those in Example 1.

[0136] The relative density of the target material prepared in this comparative example is 99%.

[0137] Compared with Example 1, in this comparative example, due to the excessively high pressure during the spark plasma sintering process, the grains are abnormally enlarged, the density of the material is reduced, and ultimately the relative density of the prepared target material is lower than that of Example 1.

[0138] Comparative Example 6

[0139] The main difference between this comparative example and Example 1 is that in step S3, the heat preservation and pressure holding time of the spark plasma sintering process is 10 minutes, and the remaining operating steps and technical parameters are the same as those of Example 1.

[0140] The relative density of the target material prepared in this comparative example is 93%.

[0141] Compared with Example 1, in this comparative example, since the heat preservation and pressure holding time during the spark plasma sintering process is shorter, the bonding between the powder particles may not be sufficient, resulting in low density of the material, and ultimately making the relative density of the prepared target material much lower than that of Example 1.

[0142] Comparative Example 7

[0143] The main difference between this comparative example and Example 1 is that in step S3, the pre-sintering temperature is 500° C., and the remaining operating steps and technical parameters are the same as those in Example 1.

[0144] The relative density of the target material prepared in this comparative example is 97%.

[0145] Compared with Example 1, in this comparative example, due to the overly high pre-sintering temperature, some grains grow abnormally, thereby reducing the density of the material, and ultimately resulting in the relative density of the prepared target material being much lower than that of Example 1.

[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a FeCoNiCuVZrAl target material, characterized in that: The steps include: S1. Preparation of alloy powder: preparing alloy powder by gas atomization of alloy liquid; S2, powder post-processing: the alloy powder obtained by gas atomization is sieved and then mixed to obtain a mixed powder; S3, plasma sintering: pre-sintering the mixed powder obtained in S2, and then plasma sintering to obtain a blank; S4, machining: machining the blank processed in step S3, and obtaining a FeCoNiCuVZrAl target after cleaning.

2. The method for preparing the FeCoNiCuVZrAl target material according to claim 1, characterized in that: The atomic percentages of Fe, Co, Ni, Cu, V, Zr and Al elements in the alloy liquid are all 5% to 35%.

3. The method for preparing the FeCoNiCuVZrAl target material according to claim 1, characterized in that: The atomic percentages of the elements in the alloy liquid are: Fe: 10-15%, Co: 10-15%, Ni: 10-15%, Cu: 12-18%, V: 10-15%, Zr: 20-25%, Al: 5-10%.

4. The method for preparing the FeCoNiCuVZrAl target material according to claim 1, characterized in that: In step S1, the alloy liquid is obtained by melting the alloy raw materials; Preferably, the alloy raw materials include Fe, Co, Ni, Cu, V, Zr and Al metal elements with a purity of 3N; Preferably, the smelting includes: a temperature of 2100-2200° C., a holding time of 10-20 min, and a vacuum degree of (0.001-0.01) Pa.

5. The method for preparing the FeCoNiCuVZrAl target material according to claim 1, characterized in that: In step S2, aerosolization specifically includes the following steps: In the vacuum atomization chamber, the inert gas breaks the alloy liquid into small droplets through the annular atomization nozzle, and the alloy powder is obtained after cooling; And / or, in step S2, sieving refers to sieving through a 300-350 mesh sieve.

6. The method for preparing the FeCoNiCuVZrAl target material according to claim 5, characterized in that: Aerosolization conditions include: The inert gas is argon or helium, the gas pressure is 5-15MPa, and the vacuum degree is (0.001-0.01)Pa; The particle size of the alloy powder obtained by gas atomization is 325-500 mesh.

7. The method for preparing the FeCoNiCuVZrAl target material according to claim 1, characterized in that: Step S3 specifically includes the following steps: The mixed powder prepared by S2 is loaded into a mold, vacuumed, pre-sintered, and then heated for spark plasma sintering.

8. The method for preparing the FeCoNiCuVZrAl target material according to claim 7, characterized in that: The mold is a graphite mold; the vacuum degree is ≤5Pa; And / or, the pre-sintering temperature is 400-450°C, the time is 10-15min, and the heating rate is 5-10°C / s; And / or, the spark plasma sintering temperature is 850-1050° C., the pressure is 30-35 MPa, the heat preservation and pressure holding time is 15-25 min, the heating rate is 5-10° C. / s, the pulse current is 1500-2500 A, and the pulse duration is 5-20 ms.

9. The method for preparing the FeCoNiCuVZrAl target material according to claim 1, characterized in that: In step S4, the machining includes one or more of cutting, turning or grinding.

10. A FeCoNiCuVZrAl target material obtained by the method for preparing a FeCoNiCuVZrAl target material according to any one of claims 1 to 9, characterized in that: The relative density of the FeCoNiCuVZrAl target material is ≥99%.